Peran Instrumen Keuangan Negara Cash Waqf Linked Sukuk Dalam Meningkatkan Pembiayaan Ekspor UMKM Indonesia - Annisa Rahma Febriyanti; Dian Ghani Reza Dasangga (El-Jizya: Jurnal Ekonomi Islam)
The aim of this research is to examine the role of the Cash Waqf Linked Sukuk instrument in increasing export financing for Indonesian MSMEs. This research employs a descriptive qualitative approach using secondary data obtained from literature studies. Cash waqf can be utilized not only in religious-based domains but also in productive economic sectors. In the context of developing Indonesian export trade, Islamic financial instruments, namely CWLS, serve as a source of funding for the government and are channeled to the Indonesian Export Financing (LPEI) Institution for financing MSMEs based on Sharia principles. Export financing will be repaid to LPEI which will be distributed to the government in the form of taxes, non-tax deductions and a share of government profits. On the other hand, the government provides periodic returns to BWI which are then distributed to Nadzir to be managed for social interests.